A certain richness: Dialogues with and within the use of photography in the work of popular educator / Daphne Uras - Uras, Daphne (1996)
Laying the Groundwork: The Freirean Philosophy and Principles Underlying Popular Education, building 0n or Breaking Down A Freirean Groundwork?, Feminist Critiques of Freirean/ Critical Pedagogy, a Rich Dialogue (Part One): Interaction Between, Deborah Brandt's Use of Photography in Popular Education, and Freirean/Critical Pedagogical Principles, A Rich Dialogue (Part Two): Interaction Between, Deborah Brandt's Use of Photography in Popular Education, and the Principles and Feminist Critiques of Popular, Education.